FUNGSI TRADISI MAGOAK-GOAKAN BAGI MASYARAKAT DI BANJAR SURAKARMA, DESA KINTAMANI, KECAMATAN KINTAMANI, KABUPATEN BANGLI - Diah Desi Sentana; Made Susila Putra; I Kadek Ruminten (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Hinduism has three basic frameworks, namely tattwa/philosophy, ethics/ethics, and rituals/rituals used by Hindus as a basis for practicing its teachings in daily life. Hindu faith is manifested in the form of ceremonies as a form of devotional worship before Ida Sang Hyang Widhi Wasa. The Magoak-goakan tradition is a very sacred and unique hereditary tradition that is still preserved by the community in Banjar Surakarma, Kintamani Village, Kintamani District, Bangli Regency. The magoak-goakan tradition is held during the Nyepi Desa celebration, which begins with Ngeker Desa. Ngeker Desa is a taboo that must be implemented or obeyed when it will be ahead of Nyepi Village celebrations. The functions contained in the magoak-goakan tradition are togetherness, social functions, cultural preservation functions, and religious functions. The uniqueness and sacredness of the Magoak-goakan tradition, contained socio-religious values so that this tradition is routinely carried out by the community in order to create a harmonious relationship between humans and gods, humans and humans, and humans with the environment called Tri Hita Karana. The theory used by the author to dissect this problem are religious theory, structural functional theory, and value theory. This research uses qualitative research with social, cultural phenomenology approach. Data collection techniques through observation, interviews and literature studies sourced from books, journals, and theses.Keywords: fungtion, Magoak-goakan tradition